PENERAPAN MEDIA PEMBELAJARAN WORDWALL TERHADAP PENINGKATAN HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA - Herlinawati, Herlinawati; Sheryl Mutiara Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Elementary school students' difficulties in understanding mathematics are often exacerbated by the minimal use of interactive learning media. The use of media such as Wordwall, which combines educational games, is considered to be able to increase student engagement and support a more enjoyable learning process. This study aims to determine the effect of Wordwall on improving elementary school students' mathematics learning outcomes. The method used is a qualitative literature review with the PRISMA approach. From the results of searching 100 articles, 18 articles were selected that met the criteria: relevant to mathematics learning in elementary school, published in scientific journals in the last five years, and focused on the use of Wordwall. The results of the study showed that Wordwall was effective in improving elementary school students' understanding of concepts and mathematics learning outcomes. Thus, Wordwall can be an appropriate alternative media to support interactive and meaningful mathematics learning in elementary school.